Investigation of antioxidant and antibacterial effects of citrus fruits peels extracts using different extracting agents: Phytochemical analysis with in silico studies. Issue 4 (April 2023) - Saleem, Muhammad; Durani, Arjumand Iqbal; Asari, Asnuzilawati; Ahmed, Mahmood; Ahmad, Muhammad; Yousaf, Numan; Muddassar, Muhammad
Abstract: The peels extracted from various citrus species are major source of phenols, flavonoids and anti-microbial agents. The purpose of this study was a detailed investigation of the phytochemical and pharmacological character of the ethanolic (80%), methanolic and acetone extracts of the peel of local variants of orange (lemon, grape fruit, mousami, fruiter, and shikri malta). The extracts were studied to find out the total phenolic contents (TPC), and total flavonoids (TF) present. The antioxidant activities were assessed by 2, 2-diphenyl-1-picrylhydrazyl (DPPH) scavenging effect, and the reducing power was determined through free radical scavenging activity (FRAP) assays. The sensitivity of four bacterial strains to peels extracts was examined by applying the diffusion disc on agar medium method. It was found that ethanol was the best extracting agent for TPC and TF in fruit peels under study. The highest TPC (21.33 ± 0.06 mg GAE/g) was quantified in orange peels, whereas fruiter contained the lowest TPC (20.40 ± 0.03 mg GAE/g) in ethanolic extract. The highest amount of TF (2.02 ± 0.08 mg QE/g) was quantified in lemon peels, whereas shikri malta contained lowest quantity of TF (1.04 ± 0.02 mg QE/g). The highest free radical scavenging activity (93.1%) of DPPH was exhibited by lemon peels, whereas the least activity (78.6%) was shown by mousami peels. Ethanolic extract of orange peels demonstrated more reducing power while showing an absorption of 1.98, followed by methanolic (1.11) and acetone (0.81) extracts. The inhibition effect of methanolic extract of lemon peels (inhibition zone = 18 mm) against B. subtilis was considerable and comparable to that of ciprofloxacin. Gas chromatography/mass spectrometry (GC/MS) was used to detect the compounds in ethanolic extract and up to 14 compounds were detected. These compounds were also assessed for their docking scores. Plausible binding modes with polyphenol oxidase and four best compounds were selected for molecular dynamics (MD) simulation to analyze their structural stability with receptor.